Policing and Equal Protection - Rosenthal, Lawrence (2015)
For urban policing, it is the best of times and the worst of times. The innovative policing techniques that have come into widespread use over the past decade are credited by many with producing significant reductions in urban crime. The vocal and numerous critics of these tactics, however, claim that the cure has been worse than the disease